New MRI contrast agents based on silicon nanotubes loaded with superparamagnetic iron oxide nanoparticles. Issue 8 (1st August 2018) - Gonzalez-Rodriguez, Roberto; Granitzer, Petra; Rumpf, Klemens; Coffer, Jeffery L.
Abstract : This article describes the preparation and fundamental properties of a new possible material as a magnetic resonance imaging contrast agent based on the incorporation of preformed iron oxide (Fe3 O4 ) nanocrystals into hollow silicon nanotubes (Si NTs). Specifically, superparamagnetic Fe3 O4 nanoparticles of two different average sizes (5 nm and 8 nm) were loaded into Si NTs of two different shell thicknesses (40 nm and 70 nm). To achieve proper aqueous solubility, the NTs were functionalized with an outer polyethylene glycol-diacid (600) moiety via an aminopropyl linkage. Relaxometry parameters r 1 and r 2 were measured, with the corresponding r 2 / r 1 ratios in phosphate buffered saline confirming the expected negative contrast agent behaviour for these materials. For a given nanocrystal size, the observed r 2 values are found to be inversely proportional to NT wall thickness, thereby demonstrating the role of nanostructured silicon template on associated relaxometry properties.